Three new isobenzofuranone derivatives from the fruiting bodies of Hericium erinaceus. Issue 2 (1st February 2017) - Wang, Xu-Li; Gao, Jie; Li, Jing; Long, Hong-Ping; Xu, Ping-Sheng; Xu, Kang-Ping; Tan, Gui-Shan
Abstract: Three new isobenzofuranone derivatives erinaceolactones D-F (1–3 ), together with four known ones (4–7 ), were isolated from the fruiting bodies of Hericium erinaceus . Their structures were determined on the basis of comprehensive spectroscopic analyses including UV, 1D, 2D NMR and HR-TOF-MS. The absolute configuration of erinaceolactone D (1 ) and erinaceolactone E (2 ) were assigned by comparing their specific rotation with those of analogs in literatures. The four known compounds were isomers with each other and were isolated simultaneously for the first time.